Analysis of the performance of an integrated multistage helical coil heat transfer device and passive cooling windcatcher for buildings in hot climates. (1st May 2022) - Pelletier, Kate; Calautit, John
Abstract: In a world of increasing population, a pending global energy crisis and the worsening impact of global warming and climate change, there needs to be a focus on re-designing building services to protect occupants at a low-energy cost. Traditional Heating, Ventilation and Air-Conditioning (HVAC) systems do not serve the future of the built environment as they rely on fans which typically constitute 25% of a building's energy consumption. Additionally, even the energy-saving strategies such as using recirculated air in mechanical ventilation systems have posed an occupancy wellbeing issue in the wake of the Covid-19 pandemic by promoting the spread of airborne disease. Therefore, natural ventilation technologies, such as windcatchers, present an advantage over mechanical systems from energy consumption and occupancy wellbeing perspectives. This paper presents the development of a multistage windcatcher with Helical Coil Heat Transfer Device (HCHTD) to enhance its cooling performance for buildings located in hot climates. The evaluation of the ventilation and cooling performance of the windcatcher with HCHTD, through a Computational Fluid Dynamics (CFD) model, includes geometric parametric studies, operating condition analyses and ventilation requirement assessment. The modelling approach was validated using previous works data, resulting in good agreement. This novel concept achieved a noteworthy range of cooling of 8.6 K–14.25 K for a range of wind speeds of 1–4 m/s and a temperature of 39°C, based on typical hot conditions in Australia. The focus of the study was to assess the impact of geometry compactness on the cooling and ventilation performance of the windcatcher with HCHTD. The outcome is that the novel helical coil heat transfer device could offer competitive cooling whilst meeting fresh air requirements, even at low wind speeds, compared to a windcatcher with a straight cylindrical heat transfer device. Graphical abstract: Image 1 Highlights: Enhancement of the performance of windcatchers using helical coil type heat transfer devices. Numerical modelling was used to evaluate using the ventilation and thermal performance. Cooling performance-enhanced using a multi-stage design for the heat transfer devices. Parametric analysis of the helical coil type heat transfer devices was carried out. The viability of the proposed technology was explored based on typical hot conditions in Australia.